A defined metabolic state in pre B cells governs B-cell development and is counterbalanced by Swiprosin-2/EFhd1 - Stein, Merle; Dütting, Sebastian; Mougiakakos, Dimitrios; Boesl, Michael R.; Fritsch, Kristin; Reimer, Dorothea; Urbanczyk, Sophia; Steinmetz, Tobit; Schuh, Wolfgang; Bozec, Aline; Winkler, Thomas; Jäck, Hans-Martin; et al. (Cell Death and Differentiation, 2017)
B-cell development in the bone marrow comprises proliferative and resting phases in different niches. We asked whether B-cell metabolism relates to these changes. Compared to pro B and small pre B cells, large pre B cells revealed the highest glucose uptake and ROS but not mitochondrial mass, whereas small pre B cells exhibited the lowest mitochondrial membrane potential. Small pre B cells from Rag1;33.C9 μ heavy chain knock-in mice revealed decreased glycolysis (ECAR) and mitochondrial spare capacity compared to pro B cells from Rag1 mice. We were interested in the step regulating this metabolic switch from pro to pre B cells and uncovered that Swiprosin-2/EFhd1, a Ca-binding protein of the inner mitochondrial membrane involved in Ca-induced mitoflashes, is expressed in pro B cells, but downregulated by surface pre B-cell receptor expression. Knockdown and knockout of EFhd1 in 38B9 pro B cells decreased the oxidative phosphorylation/glycolysis (OCR/ECAR) ratio by increasing glycolysis, glycolytic capacity and reserve. Prolonged expression of EFhd1 in EFhd1 transgenic mice beyond the pro B cell stage increased expression of the mitochondrial co-activator PGC-1α in primary pre B cells, but reduced mitochondrial ATP production at the pro to pre B cell transition in IL-7 cultures. Transgenic EFhd1 expression caused a B-cell intrinsic developmental disadvantage for pro and pre B cells. Hence, coordinated expression of EFhd1 in pro B cells and by the pre BCR regulates metabolic changes and pro/pre B-cell development.Cell Death and Differentiation advance online publication, 19 May 2017; doi:10.1038/cdd.2017.52.

Assessing metabolic demands in B cells - Mielenz, Dirk; Urbanczyk, Sophia; Stein, Merle; Reimer, Dorothea; Winkler, Thomas; Jäck, Hans-Martin (2017)
EVALuna2:13657

B Cell Speed and B-FDC Contacts in Germinal Centers Determine Plasma Cell Output via Swiprosin-1/EFhd2 - Reimer, Dorothea; Meyer-Hermann, Michael; Rakhymzhan, Asylkhan; Steinmetz, Tobit; Tripal, Philipp; Thomas, Jana; Böttcher, Martin; Mougiakakos, Dimitrios; Schulz, Sebastian; Urbanczyk, Sophia; Hauser, Anja E.; Niesner, Raluca A.; et al. (Cell Reports, 2020)
Plasma cells secreting affinity-matured antibodies develop in germinal centers (GCs), where B cells migrate persistently and directionally over defined periods of time. How modes of GC B cell migration influence plasma cell development remained unclear. Through genetic deletion of the F-actin bundling protein Swiprosin-1/EF-hand domain family member 2 (EFhd2) and by two-photon microscopy, we show that EFhd2 restrains B cell speed in GCs and hapten-specific plasma cell output. Modeling the GC reaction reveals that increasing GC B cell speed promotes plasma cell generation. Lack of EFhd2 also reduces contacts of GC B cells with follicular dendritic cells in vivo. Computational modeling uncovers that both GC output and antibody affinity depend quantitatively on contacts of GC B cells with follicular dendritic cells when B cells migrate more persistently. Collectively, our data explain how GC B cells integrate speed and persistence of cell migration with B cell receptor affinity.
CRIS-Team Scopus Importer:2020-08-14
Keywords: actin cytoskeleton; B cell receptor; differentiation; follicular dendritic cell; germinal center; migration; plasma cell; selection; Swiprosin-1/EFhd2; synapse

Essential respiratory chain subunits encoded by mitochondrial DNA control plasma cell development - Urbanczyk, Sophia; Baris, Olivier; Mougiakakos, Dimitrios; Wiesner, Rudolf; Jäck, Hans-Martin; Mielenz, Dirk (JOURNAL OF IMMUNOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-08

Guidelines for the use of flow cytometry and cell sorting in immunological studies (second edition) - Cossarizza, Andrea; Acs, Andreas; Adam, Dieter; Adam-Klages, Sabine; Agace, William W.; Aghaeepour, Nima; Akdis, Mübeccel; Allez, Matthieu; Almeida, Larissa Nogueira; Alvisi, Giorgia; Anderson, Graham; Andrä, Immanuel; et al. (European Journal of Immunology, 2019)
These guidelines are a consensus work of a considerable number of members of the immunology and flow cytometry community. They provide the theory and key practical aspects of flow cytometry enabling immunologists to avoid the common errors that often undermine immunological data. Notably, there are comprehensive sections of all major immune cell types with helpful Tables detailing phenotypes in murine and human cells. The latest flow cytometry techniques and applications are also described, featuring examples of the data that can be generated and, importantly, how the data can be analysed. Furthermore, there are sections detailing tips, tricks and pitfalls to avoid, all written and peer-reviewed by leading experts in the field, making this an essential research companion.
CRIS-Team Scopus Importer:2019-10-29

Influence of Swiprosin2/EFhd1 on the metabolic control of B cell differentiation and humoral immunity - Urbanczyk, Sophia; Stein, Marcello F.; Duetting, S.; Mougiakakos, Dimitrios; Boesl, M.; Reimer, Dorothea; Steinmetz, Tobit; Schuh, Wolfgang; Bozec, Aline; Winkler, Thomas; Jäck, Hans-Martin; Mielenz, Dirk (2017)
EVALuna2:13653

Metabolic impairment of non-small cell lung cancers by mitochondrial HSPD1 targeting - Parma, Beatrice; Ramesh, Vignesh; Gollavilli, Paradesi Naidu; Siddiqui, Aarif; Pinna, Luisa; Schwab, Annemarie; Marschall, Sabine; Zhang, Shuman; Pilarsky, Christian; Napoli, Francesca; Volante, Marco; Urbanczyk, Sophia; et al. (Journal of Experimental & Clinical Cancer Research, 2021)
Background The identification of novel targets is of paramount importance to develop more effective drugs and improve the treatment of non-small cell lung cancer (NSCLC), the leading cause of cancer-related deaths worldwide. Since cells alter their metabolic rewiring during tumorigenesis and along cancer progression, targeting key metabolic players and metabolism-associated proteins represents a valuable approach with a high therapeutic potential. Metabolic fitness relies on the functionality of heat shock proteins (HSPs), molecular chaperones that facilitate the correct folding of metabolism enzymes and their assembly in macromolecular structures. Methods Gene fitness was determined by bioinformatics analysis from available datasets from genetic screenings. HSPD1 expression was evaluated by immunohistochemistry from formalin-fixed paraffin-embedded tissues from NSCLC patients. Real-time proliferation assays with and without cytotoxicity reagents, colony formation assays and cell cycle analyses were used to monitor growth and drug sensitivity of different NSCLC cells in vitro. In vivo growth was monitored with subcutaneous injections in immune-deficient mice. Cell metabolic activity was analyzed through extracellular metabolic flux analysis. Specific knockouts were introduced by CRISPR/Cas9. Results We show heat shock protein family D member 1 (HSPD1 or HSP60) as a survival gene ubiquitously expressed in NSCLC and associated with poor patients' prognosis. HSPD1 knockdown or its chemical disruption by the small molecule KHS101 induces a drastic breakdown of oxidative phosphorylation, and suppresses cell proliferation both in vitro and in vivo. By combining drug profiling with transcriptomics and through a whole-genome CRISPR/Cas9 screen, we demonstrate that HSPD1-targeted anti-cancer effects are dependent on oxidative phosphorylation and validated molecular determinants of KHS101 sensitivity, in particular, the creatine-transporter SLC6A8 and the subunit of the cytochrome c oxidase complex COX5B. Conclusions These results highlight mitochondrial metabolism as an attractive target and HSPD1 as a potential theranostic marker for developing therapies to combat NSCLC.
CRIS-Team WoS Importer:2021-08-20

Mitochondrial metabolism influences plasma cell differentiation - Urbanczyk, Sophia; Baris, O.; Reimer, Dorothea; Steinmetz, Tobit; Mougiakakos, Dimitrios; Wiesner, R.; Mielenz, Dirk (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Mitochondrial respiration in B lymphocytes is essential for humoral immunity by controlling the flux of the TCA cycle - Urbanczyk, Sophia; Baris, Olivier R.; Hofmann, Jörg; Taudte, Verena; Guegen, Naïg; Golombek, Florian; Castiglione, Kathrin; Meng, Xianyi; Bozec, Aline; Thomas, Jana; Weckwerth, Leonie; Mougiakakos, Dimitrios; et al. (Cell Reports, 2022)
To elucidate the function of oxidative phosphorylation (OxPhos) during B cell differentiation, we employ CD23Cre-driven expression of the dominant-negative K320E mutant of the mitochondrial helicase Twinkle (DNT). DNT-expression depletes mitochondrial DNA during B cell maturation, reduces the abundance of respiratory chain protein subunits encoded by mitochondrial DNA, and, consequently, respiratory chain super-complexes in activated B cells. Whereas B cell development in DNT mice is normal, B cell proliferation, germinal centers, class switch to IgG, plasma cell maturation, and T cell-dependent as well as T cell-independent humoral immunity are diminished. DNT expression dampens OxPhos but increases glycolysis in lipopolysaccharide and B cell receptor-activated cells. Lipopolysaccharide-activated DNT-B cells exhibit altered metabolites of glycolysis, the pentose phosphate pathway, and the tricarboxylic acid cycle and a lower amount of phosphatidic acid. Consequently, mTORC1 activity and BLIMP1 induction are curtailed, whereas HIF1α is stabilized. Hence, mitochondrial DNA controls the metabolism of activated B cells via OxPhos to foster humoral immunity.
CRIS-Team Scopus Importer:2022-06-17
Keywords: B lymphocyte; class switch recombination; CP: Immunology; germinal center; HIF1; hypoxia inducible factor 1; mammalian target of Rapamycin; mitochondrial DNA; mitochondrial respiration; mTOR; oxidative phosphorylation; phosphatidic acid; plasma cell; TCA cycle

Proteasomal degradation induced by DPP9-mediated processing competes with mitochondrial protein import - Finger, Yannik; Habich, Markus; Gerlich, Sarah; Urbanczyk, Sophia; van de Logt, Erik; Koch, Julian; Schu, Laura; Lapacz, Kim Jasmin; Ali, Muna; Petrungaro, Carmelina; Salscheider, Silja Lucia; Pichlo, Christian; et al. (EMBO Journal, 2020)
Plasticity of the proteome is critical to adapt to varying conditions. Control of mitochondrial protein import contributes to this plasticity. Here, we identified a pathway that regulates mitochondrial protein import by regulated N-terminal processing. We demonstrate that dipeptidyl peptidases 8/9 (DPP8/9) mediate the N-terminal processing of adenylate kinase 2 (AK2) en route to mitochondria. We show that AK2 is a substrate of the mitochondrial disulfide relay, thus lacking an N-terminal mitochondrial targeting sequence and undergoing comparatively slow import. DPP9-mediated processing of AK2 induces its rapid proteasomal degradation and prevents cytosolic accumulation of enzymatically active AK2. Besides AK2, we identify more than 100 mitochondrial proteins with putative DPP8/9 recognition sites and demonstrate that DPP8/9 influence the cellular levels of a number of these proteins. Collectively, we provide in this study a conceptual framework on how regulated cytosolic processing controls levels of mitochondrial proteins as well as their dual localization to mitochondria and other compartments.
CRIS-Team Scopus Importer:2020-08-28
Keywords: adenylate kinase 2; dipeptidyl peptidase 9; MIA40; mitochondrial protein import; quality control

Regulation of Energy Metabolism during Early B Lymphocyte Development - Urbanczyk, Sophia; Stein, Merle; Schuh, Wolfgang; Jäck, Hans-Martin; Mougiakakos, Dimitrios; Mielenz, Dirk (International Journal of Molecular Sciences, 2018)
The most important feature of humoral immunity is the adaptation of the diversity of newly generated B cell receptors, that is, the antigen receptor repertoire, to the body's own and foreign structures. This includes the transient propagation of B progenitor cells and B cells, which possess receptors that are positively selected via anabolic signalling pathways under highly competitive conditions. The metabolic regulation of early B-cell development thus has important consequences for the expansion of normal or malignant pre-B cell clones. In addition, cellular senescence programs based on the expression of B cell identity factors, such as Pax5, act to prevent excessive proliferation and cellular deviation. Here, we review the basic mechanisms underlying the regulation of glycolysis and oxidative phosphorylation during early B cell development in bone marrow. We focus on the regulation of glycolysis and mitochondrial oxidative phosphorylation at the transition from non-transformed pro- to pre-B cells and discuss some ongoing issues. We introduce Swiprosin-2/EFhd1 as a potential regulator of glycolysis in pro-B cells that has also been linked to Ca2+-mediated mitoflashes. Mitoflashes are bioenergetic mitochondrial events that control mitochondrial metabolism and signalling in both healthy and disease states. We discuss how Ca2+ fluctuations in pro- and pre-B cells may translate into mitoflashes in early B cells and speculate about the consequences of these changes.
EVALuna2:35105

TFG is upregulated during plasma cell differentiation and regulates apoptosis, ER stress and autophagy in a B cell line - Steinmetz, Tobit; Reimer, Dorothea; Urbanczyk, Sophia; Schlötzer-Schrehardt, Ursula; Winkler, Thomas; Jäck, Hans-Martin; Mielenz, Dirk (JOURNAL OF IMMUNOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-08